Etika Bisnis Islami dalam Perspektif Fiqih Muamalah Antara Hukum, Moral, dan Spiritualitas - Rudi Hartono I; Maisarah Maisarah; Pira Yulisman; Recy Fitrya Murni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to examine in depth the foundations of business ethics in Islam through the view of Fiqh Muamalah. Islamic business ethics is not only limited to the formal legal aspects of transactions, but also includes moral and spiritual dimensions derived from the Qur'an and Sunnah. Fiqh Muamalah is defined as a branch of jurisprudence that regulates social and economic interactions, offering a comprehensive framework for understanding and implementing ethical principles in business activities. The discussion in this article covers the fundamental principles of Islamic business ethics, its implementation in various aspects of business, and its relevance in the context of modern economics. Through an in-depth analysis, this article seeks to provide a comprehensive understanding of how Islamic values can be a solid foundation for fair, transparent, and responsible business practices.